(untitled) (Research, Society and Development, 2021)
Objective: To analyze the hospital care capacity through requesting ICU beds in a reference hospital. Method: cross-sectional study, carried out at in a hospital located in the municipality of Sobral-CE, from January to march 2019. The sample was 489 patients. The primary outcome was the attendance capacity, regarding the availability of ICU beds, dichotomized as unattended and attended. Associative variables analyzed were: sex, age, origin, diagnosis, priority, number of requests, waiting time and service situation. The Wald chi-square test and multiple regression were used for data analysis. Results: a significant association was identified with between primary outcome and age, priority, clinical diagnosis, service situation and waiting time. Conclusion: the service capacity was restricted to solving the problems of the municipality, headquarters and surroundings population, in relation to intensive care, and results indicated a low supply of beds in relation to the demand for requests.